Evaluating the interstitial lung disease multidisciplinary meeting: a survey of expert centres. Issue 1 (December 2016) - Jo, Helen; Corte, Tamera; Moodley, Yuben; Levin, Kovi; Westall, Glen; Hopkins, Peter; Chambers, Daniel; Glaspole, Ian
Abstract Background Multidisciplinary meetings (MDM) are the current "gold standard" in interstitial lung disease (ILD) diagnosis and comprise inter-disciplinary discussion of multiple forms of information to provide diagnostic and management outputs. Although bias could be potentially inserted at any step in the discussion process, to date there has been no consensus regarding the appropriate constitution and governance of MDM. We sought to determine the features of ILD MDMs based within ILD centres of excellence around the world. Methods An internet based questionnaire was sent to twelve expert centres in Europe, North America, and Australia seeking information regarding the structure and governance of their MDM. Data was analysed for consistent themes and points of contrast. Results Responses were received from 10 out of 12 centres. Similarities were demonstrated with regards to contributing attendees, meeting frequency and case numbers reviewed. Significant heterogeneity in attendee speciality group type, quantity and method of data presentation, approach to diagnosis formulation and documentation, and information provision was apparent. Conclusions The constitution of ILD MDMs differs considerably between expert centres. Such differences may result in discordant outcomes, and emphasise the need for further evidence regarding the appropriate constitution and governance of ILD MDMs.